2021
DOI: 10.1111/tbj.14186
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive literature review of patient‐reported outcome measures (PROMs) among common breast reconstruction options: What types of breast reconstruction score well?

Abstract: Purpose Breast cancer continues to be the most prevalent cancer affecting women. Many reconstructive options exist after oncologic resection. Breast reconstruction can have a lasting impact on many areas of the patient's life, and therefore, a high consideration for patient satisfaction is crucial. Patient‐reported outcome measures (PROMs) provide an important tool in the evaluation of different surgical methodologies. The aim of this comprehensive systematic review is to look at various surgical modalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
(45 reference statements)
0
33
2
Order By: Relevance
“…17,18 Oncoplastic surgery showed the most favorable PROMs when compared to other reconstructive modalities. 19 Its oncologic utility lies in the ability to perform a large partial mastectomy, resulting in a decreased positive margin rate, while utilizing local tissue rearrangement to reconstruct the breast. OPS can be further categorized into level 1 volume displacement, level 2 volume displacement, and volume replacement based on the American Society of Breast Surgeons definitions.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Oncoplastic surgery showed the most favorable PROMs when compared to other reconstructive modalities. 19 Its oncologic utility lies in the ability to perform a large partial mastectomy, resulting in a decreased positive margin rate, while utilizing local tissue rearrangement to reconstruct the breast. OPS can be further categorized into level 1 volume displacement, level 2 volume displacement, and volume replacement based on the American Society of Breast Surgeons definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Other available options are the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30, and the EORTC QLQ-BR23 questionnaires [89-91]. In a literature review by Char et al [92], BREAST-Q data showed OBCS had significantly higher scores than mastectomy regardless of the type of the reconstruction performed. In another systematic review performed by Aristokleous and Saddiq [93] evaluating patients’ QOL, OBCS was found to be associated with a trend toward better patient QOL than BCS alone.…”
Section: Qol Outcomes Assessmentmentioning
confidence: 99%
“…Recent studies have demonstrated that oncoplastic surgery in general has higher patient-reported outcomes compared with mastectomy operations. 8 Nevertheless, like doctors, patients are unique individuals and surgical plans need to be formulated with empathy, support, and evidence-based discussion, with focus on patient-specific preferences (size preference of breast, etc.). Furthermore, the relative fiscal impact of each choice with specific regards to financial toxicity to the patient has yet to be studied in detail, but is definitely a significant real-world issue that impacts decision-making.…”
Section: Tufts Medical Center Bostonmentioning
confidence: 99%